Association of hairdressing with cancer and reproductive diseases: A systematic review - Babic, Zeljka; Macan, Marija; Franic, Zrinka; Hallmann, Sarah; Havmose, Martin S.; Johansen, Jeanne D.; John, Swen M.; Symanzik, Cara; Uter, Wolfgang; Weinert, Patricia; Van Der Molen, Henk F.; Kezic, Sanja; et al. (Journal of Occupational Health, 2022)
Objectives To review recent epidemiological studies investigating carcinogenic or reprotoxic effects among hairdressers who seem to be at greater risk for systemic adverse effects of chemicals released from hair care products than consumers. Methods A systematic review according to the PRISMA-P guidelines was performed and included studies published from 2000 to August 2021, in which cancer or adverse reproductive effects were diagnosed in 1995 and onward. Data were synthetized qualitatively due to the small number of studies, heterogeneity of study designs, outcomes, and methods. Results Four studies investigating cancer frequencies and six studies investigating effects on reproduction among hairdressers were identified. All were of good quality and with low risk of bias. Only one of the four studies found an increased risk of cancer reporting nine times higher odds for bladder cancer in hairdressers than the population-based controls. Three other studies investigating bladder and lung cancer, and non-Hodgins lymphoma did not find an increased risk in hairdressers. Regarding reprotoxic effects, numerous outcomes were investigated including menstrual disorders, congenital malformations, fetal loss, small-for-gestational age newborns, preterm delivery, and infertility. Increased risk was found for ventricular septal defect in newborns of fathers working as hairdressers. Furthermore, several indices of poor neonatal or maternal health were significantly associated with mothers working as hairdresser. Conclusions Despite the scarce evidence that hairdressers are at increased risk of carcinogenic or reprotoxic effects related to their trade, such health risks cannot be ruled out. Therefore, preventive efforts to diminish occupational exposures to hairdressing chemicals should be targeted.
CRIS-Team WoS Importer:2022-09-02